ARABIC LANGUAGE LEARNING BASED ON CHARACTER EDUCATION - Fitri Ariati; Retoliah, Retoliah; Zulfikri, Zulfikri (Program Studi Pendidikan Bahasa Arab (PBA), Universitas Islam Negeri Datokarama Palu, 2024)
This article explores the integration of character education into Arabic language learning in Indonesian education. Character education, foundational in Indonesian education, has gained renewed attention due to societal moral crises, prompting a closer examination of its implementation. The research employs library research methodology, focusing on literature related to Arabic language learning and character education. It identifies methods and approaches for integrating character education into Arabic language learning, emphasizing the significance of Arabic as the language of the Quran and Hadith, fundamental texts in Islam containing guidance on character formation. The article discusses the nature of Arabic language learning, goals, learning systems, and character education concepts, highlighting essential character traits and values. Strategies for character education and methods for fostering character development in students are explored. Moreover, the article outlines character-based Arabic language learning activities, from planning to evaluation stages, underscoring the role of teaching materials and educators as role models. Ultimately, it concludes that integrating character education into Arabic language learning can contribute significantly to the holistic development of learners, instilling moral values and ethical principles derived from Islamic teachings.